(untitled) (Panacea Journal of Medical Sciences, 2024)
Background: Meckel’s diverticulum (MD) develops from persistent omphalomesenteric duct and is an uncommon finding in females. Our aim is to report the incidence of finding of MD in cadavers and to study its gross and histological feature. Materials and Methods: The observational study was conducted in 60 cadavers over a period of nine years. In the present study a meckel’s diverticulum was detected in sixty years old female cadaver. Result: The diverticulum was 63 cm proximal to ileocecal junction. It was 6 cm in length and 3.5cm in width and its tip free from any connections. Histologically, it showed four layers of ileum and patchy areas of coagulative necrosis in the mucosa. Conclusion: These uneventful Meckel’s diverticulum findings of meckel’s diverticulum should be reported from time to time in particular population which may be beneficial for the surgeons and radiologists.